A qualitative systematic review of burden among patients with hemodialysis - Ni Made Sekar Sari; Ni Kadek Arie Octarini; Ika Yuni Widyawati; Elida Ulfiana (Journal of Holistic Nursing Science, 2022)
The study is to explore the burden experienced during dialysis care integration in a patient’s life. A systematic search was employed and focused on qualitative studies. We searched some reference lists of eligible studies published in 2018-2022. We followed the PRISMA guidelines, and the analysis employed a meta-ethnography study. We identified that the dialysis care integration burden had been perceived since the initial decision to dialysis care integration. Patients felt powerless since they were provided with no choice of medical intervention. The perceived service affordability and barriers had added more burden experience of dialysis care integration. The dialysis care integration restricts various aspects of the patient’s life: food and drink intake, mobilization, and activity. The strategy for integrated dialysis care required utilizing numerous resources to build positive coping strategies. The finding signified that dialysis patients demanded assistance from various resources to adjust to the current dialysis care. Keywords: Health burden; dyalisis care; kidney injury; chronic illness; quality of life